(untitled) (Journal of Economic Research & Business Administration, 2022)
The aim of this study is to assess the impact of information and communication technologies (ICT) on the level of women participation in the online market in Kazakhstan before and after the COVID-19 pandemic. The studies of existing concepts and economic models, domestic and foreign literary sources are based on the analysis of gender differences in the online sector. The data sources were primary in-depth semi-structured interviews with respondents and a survey among 300 women, as well as secondary data from the Bureau of National Statistics of the Republic of Kazakhstan for 2015-2020. In this scientific study, the authors propose a methodological toolkit that includes two stages of analysis: assessment of the level of ICT development in terms of gender for 2015-2020; quantitative assessment of the state and level of development of the online market in Kazakhstan. The research revealed the most popular marketplaces among women in Kazakhstan (Kaspi, Instagram, Wildberries, Flip, Aliexpress). The study showed that the COVID-19 pandemic affected the number of online purchases and their structure, as well as the digitalization processes lead to a decrease in the specialization of women in home employment and an increase in their level of participation. The research results can be used in the development of state policy for the development of women’s entrepreneurship. Key words: gender, gender economy, digitalization, ICT, online market.